Rational Invariants of the Generalized Classical Groups (Communications in Mathematical Research, 2021)
In this paper, we give transcendence bases of the rational invariants fieldsof the generalized classical groups and their subgroups B, N and T , and we alsocompute the orders of them. Furthermore, we give explicit generators for the rationalinvariants fields of the Borel subgroup and the Neron-Severi subgroup of the generallinear group.
Keywords: generalized classical group; BN-pair; invariant; finite field.